Consumers’ preferences for sweet potato in Viet Nam and implications for CGIAR market segmentation and target product profiles - Naziri, Diego; Thi Minh Hang Vu; Viet Phu Tu; Ssali, Reuben; Okello, Julius Juma; Lindqvist-Kreuze, Hannele; Polar, Vivian (CGIAR, 2024)
Cognizant of the need to refocus breeding efforts toward end-product quality traits taking into account consumer preferences and considering the rapid urbanization in South-eastern Asia, we investigated consumer preferences for sweet potato in Hanoi. Using a mixed-methods research design, we identified the most preferred and least preferred attributes of both the fresh and boiled products. We found the absence of external defects to be the main sought-after characteristic in fresh roots, followed by flavor, texture, weight, size, color, and shape. Both women and men preferred medium- to large-sized roots (with men preferring larger ones) having elongated shape and smooth peel. Women paid more attention to the color of the peel (purple or yellow preferred; white least preferred) and uniformity in root size, while men were more attracted to the firmness of the root. Regarding the boiled product, both women and men indicated mealiness and sweetness among the three most important characteristics. In addition, women prioritized smell and flavor; men, its softness. Unlike men, women indicated that the color of the flesh and the size of the root are other important requirements. The study also determined preferences and associated traits of six popular varieties. Results indicate that while these varieties largely already meet consumers’ preferences, consumers have a clear preference for a few varieties that require marginal adjustments to further increase their acceptability among the growing urban population. The findings provide insights for enhancing the current seed product market segmentation and for adjusting the existing target product profile. It is expected that this will contribute to higher and faster variety uptake and adoption and ultimately increase food security, nutrition, and livelihood opportunities in the region.